Resources in the Package C Death Certificate Service at the Population and Civil Registration Service of Sidoarjo Regency: Sumber Daya Dalam Pelayanan Paket C Akta Kematian di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo - Sakti Tia; Lailul Mursyidah (Academia Open, 2021)
The purpose of this research is to describe and analyze the service package c death certificate at the Department of Population and Civil Registration of Sidoarjo Regency. This study used a qualitative type method approach which took place in the Sidoarjo District Civil Service Office as the location of the research. This research is presented with data collection techniques through observation, interviews, and documentation. The technique of determining the informants used purposive sampling, and data analysis was carried out by data collection techniques, data reduction, data presentation, and conclusions or verification. The results of this study use the theory of public service quality which can be seen from the unfulfilled resources of the Sidoarjo Ministry of Civil Service and Civil Service, based on a review of several dimensions such as Tangible, which shows a lack of employees in the issuance of death certificates and insufficient sarpras, Reliability. (Reliability) there are SOPs stated in the Perbup), Responsiviness (Response) becomes less than optimal because the number of employees in the publishing division is only 2 (two) people and the applicant is 40 people each day, the Sidoarjo Dispendukcapil Assurance issues death certificates, KK , KTP, and Emphaty (Empathy) can be seen from the services that have met the service standards of the OPD (Regional Apparatus Organization), but it is necessary to add additional employees in the publishing department so that the service can be maximized.